First Natural Endocranial Cast of a Fossil Snake (Cretaceous of Patagonia, Argentina) - Triviño, Laura Natalia (2017)
In this study, we describe a natural endocranial cast included in a partially preserved medium‐sized skull of the Upper Cretaceous South American snake Dinilysia patagonica. The endocast is composed of sedimentary filling of the cranial cavity in which the posterior brain, the vessels, the cranial nerves, and the inner ear surrounded by delicate semicircular canals, are represented. It is simple in form, with little differentiation between the three main areas (Forebrain, Midbrain, and Hindbrain), and without flexures. The nervous system is well preserved. The posterior brain surface is smooth, except for two small prominences that make up the cerebellum. A large inner ear is preserved on the right side; it consists of a voluminous central mass, the vestibule, which occupies most of the space defined by the three semicircular canals. In particular, the lateral semicircular canal is very close to the vestibule. This characteristic, in combination with the medium to large body size of Dinilysia, its large skull and dorsally exposed orbits, and vertebrae bearing a rather high neural spine on a depressed neural arch, suggests that this snake would have had a semifossorial lifestyle.